2007
DOI: 10.1126/science.1139727
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Tholin Formation in Titan's Upper Atmosphere

Abstract: Titan's lower atmosphere has long been known to harbor organic aerosols (tholins) presumed to have been formed from simple molecules, such as methane and nitrogen (CH 4 and N 2 ). Up to now, it has been assumed that tholins were formed at altitudes of several hundred kilometers by processes as yet unobserved. Using measurements from a combination of mass/charge and energy/charge spectrometers on the Cassini spacecraft, we have obtained evidence for tholin formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
636
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 618 publications
(653 citation statements)
references
References 27 publications
17
636
0
Order By: Relevance
“…As outlined in section 2, we have employed an empirical chemical production of H 2 given by P H 2 = 1.15 × L CH 4 , which is loosely based upon the measurements of heavy hydrocarbon C:H ratios made by INMS [Waite et al, 2007;Westlake et al, 2012]. This scheme liberates significantly more H 2 than the original scheme of Bell et al [2010a], and we now examine the implications of this added H 2 production on T-GITM simulated H 2 densities and mixing ratios.…”
Section: The Impacts Of H 2 Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined in section 2, we have employed an empirical chemical production of H 2 given by P H 2 = 1.15 × L CH 4 , which is loosely based upon the measurements of heavy hydrocarbon C:H ratios made by INMS [Waite et al, 2007;Westlake et al, 2012]. This scheme liberates significantly more H 2 than the original scheme of Bell et al [2010a], and we now examine the implications of this added H 2 production on T-GITM simulated H 2 densities and mixing ratios.…”
Section: The Impacts Of H 2 Chemistrymentioning
confidence: 99%
“…an analysis of the Cassini INMS heavy hydrocarbon data by Waite et al [2007] and Westlake et al [2012], which indicate that the heavy hydrocarbons have a carbon to hydrogen ratio of roughly 1:1.7. This 1:1.7 C to H ratio suggests that 1.15 H 2 molecules are liberated for every CH 4 molecule consumed by chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between these ions and the heavy positive ion population was discussed by Waite et al (2007). They suggested that nitrogen and methane in Titan's high atmosphere would be acted on by sunlight and magnetospheric particles forming heavier but relatively simple species by dissociation and )) is not yet understood; but it may be the poorer sensitivity of IBS, or different chemical pathways for positive and negative ions.…”
Section: (D ) Negative Ions: An Unexpected Feature In Titan Encountersmentioning
confidence: 99%
“…Extrapolation of the INMS measurements (limited to mass up to 100 Da) and of CAPS data, strongly suggests that high-molecular-weight species (up to several 1,000 Da) may be present in the ionosphere. These new data-if confirmedrevolutionize the understanding of the organic processes occurring in Titan's atmosphere, with a strong implication that ionospheric chemistry plays a role in the formation of complex organic compounds in Titan's environment, which was predicted [3] but whose extent was not envisioned before [2,51].…”
Section: A Complex Prebiotic-like Chemistrymentioning
confidence: 60%
“…The direct analysis of the ionosphere by the INMS instrument during the closest Cassini flybys of Titan shows the presence of many organic species, in spite of the very high altitude (1,100-1,300 km) [51]. Extrapolation of the INMS measurements (limited to mass up to 100 Da) and of CAPS data, strongly suggests that high-molecular-weight species (up to several 1,000 Da) may be present in the ionosphere.…”
Section: A Complex Prebiotic-like Chemistrymentioning
confidence: 99%